Efficient thermomechanical analysis of functionally graded structures using the symmetric SPH method. (June 2021) - Li, Jiao; Wang, Guangchun; Liu, Shuai; Lin, Jun; Guan, Yanjin; Zhao, Guoqun; Naceur, Hakim; Coutellier, Daniel; Wu, Tao
Abstract: Tailoring the thermal and mechanical properties plays an important role in manufacturing and designing functionally graded material (FGM) which is often applied in high temperature gradient environment. The present investigation will address the basics of thermoelastic problem solved by means of a specific meshless smoothed particle hydrodynamics (SPH) method. The inconsistency of the conventional SPH method was improved by introducing the symmetric SPH (SSPH) technique, where function derivatives can be approximated by the function values in the support domain. Hence, the heat conduction and balance equations become a series of algebraic equations, which can be solved efficiently. The result accuracy achieved by the proposed approach was demonstrated in solving several numerical examples in comparison to available results in the literature. The effect of the gradation indexes on the thermoelastic behavior was also considered.